Study experiences and the post-study intentions of female international undergraduate students. Issue 2 (3rd April 2018) - Kelly, Alison; Bennett, Dawn; Giridharan, Beena; Rosenwax, Lorna
Abstract: The number of female international students is increasing exponentially, and whilst international study may engender many benefits and challenges, little is known about their intentions once they complete their studies. This article reviews the literature on female international students with specific focus on exploring post-study intentions. A scoping review of four electronic databases was completed. After applying criteria to determine suitability, 30 publications were included in the final review. Analysis revealed three key foci: (1) the rationale for studying internationally; (2) the study experience; and (3) post-study intentions. The literature illustrates that an international study experience has the potential to be a powerful transformative opportunity if positive experiences outweigh the negatives. The findings also indicate that the post-study intentions of female international students are under-researched. The article contends that attention should be given to supporting the needs of this group, with a view to maximizing post-study opportunities.